- Thread starter
- #1

#### karush

##### Well-known member

- Jan 31, 2012

- 2,929

$\tiny{mil.navy.01}$

This is on an sample entrance exam test for the Navy Academy

Use "completing the square" to rewrite

$x^2-4x+3=0$ in the form $\quad (x-c)^2=d$

a, $(x-1)^2=1$

b. $(x-2)^2=1$

c. $(x-3)^2=1$

d. $(x-2)^2=2$

e. $(x-4)^2=1$

ok I am not sure why they suggest the second transformation

This is on an sample entrance exam test for the Navy Academy

Use "completing the square" to rewrite

$x^2-4x+3=0$ in the form $\quad (x-c)^2=d$

a, $(x-1)^2=1$

b. $(x-2)^2=1$

c. $(x-3)^2=1$

d. $(x-2)^2=2$

e. $(x-4)^2=1$

ok I am not sure why they suggest the second transformation

Last edited: